Al. Spendiaryan’s Creativity in G. Tigranov’s Observations - Asatryan, Ani
Հոդվածը նվիրված է նշանավոր երաժշտագետ Գ. Տիգրանովի կողմից հայ դասական երաժշտության հիմնադիր Ալ. Սպենդիարյանի ստեղծագործությանը նվիրված դրույթներին: The article is devoted to scientific assessment, statements about the work of the founder of Armenian classical musician A. Spendiaryan, given by the famous musicologist G. Tigranov. Methods and materials: By means of historical and musicological methods we have studied G. Tigranov’s articles, notes. Analysis: We have analyzed many articles, scientific reports of G. Tigranov, dedicated to the life and work of A. Spendiaryan. Results: G.Tigranov devoted most of his scientific activity to the study of the life and work of the famous Armenian composer Al.Spendiaryan. These voluminous works have left their mark on the study of the history of Armenian music. Статья посвящена научной оценке, высказываниям о творчестве основоположника армянской классической музыки А. Спендиаряна, давшим известным музыковедом Г. Тиграновым. Методы и материалы: Статьи, заметки и выступления Г. Тигранова исследованы историко-музыковедческим методом. Анализ: Мы проанализировали множество статей, научных докладов Г.Тигранова, посвященных жизни и деятельности А. Спендиаряна. Результаты: Г.Тигранов посвятил большую часть своей научной деятельности изучению жизни и творчества известного армянского композитора Ал.Спендиаряна. Эти объемные труды оставили свой след в изучении истории армянской музыки.
Keywords: Armenian classical music